Manganese-induced neuronal apoptosis: new insights into the role of endoplasmic reticulum stress in regulating autophagy-related proteins. (15th December 2022) - Liu, Chang; Ju, Rong
Abstract: Manganese (Mn) is an essential trace element that participates in various physiological and pathological processes. However, epidemiological observations indicate that overexposure to Mn is strongly associated with neurodegenerative disorders and has been recognized as a potential risk factor of neuronal apoptosis. Many mechanisms are involved in the pathogenesis of Mn-induced neuronal apoptosis, such as reactive oxygen species generation, neuroinflammation reactions, protein accumulation, endoplasmic reticulum stress (ER stress), and autophagy, all of which collectively accelerate the process of nerve cell damage. As sophisticated cellular processes for maintaining intracellular homeostasis, ER-mediated unfolded protein response and autophagy both play bilateral roles including cell protection and cell injury under pathophysiological conditions, which might interact with each other. Although emerging evidence suggests that ER stress is involved in regulating the compensatory activation of autophagy to promote cell survival, the inherent relationship between ER stress and autophagy on Mn-induced neurotoxicity remains obscure. Here, our review focuses on discussing the existing mechanisms and connections between ER stress, autophagy, and apoptosis, which provide a new perspective on Mn-induced neuronal apoptosis, and the pathogenesis of neurodegenerative diseases. Graphical Abstract: